2010
DOI: 10.1007/s00267-010-9582-3
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Jackfruit (Artocarpus heterophyllus) Affects Group Characteristics and Use of Space by Golden-Headed Lion Tamarins (Leontopithecus chrysomelas) in Cabruca Agroforest

Abstract: Cabruca is an agroforest of cacao trees shaded by native forest trees. It is the predominant vegetation type throughout eastern part of the range of the golden-headed lion tamarins, Leontopithecus chrysomelas, an endangered primate endemic to Atlantic Forest. Understanding how lion tamarins use this agroforest is a conservation priority. To address this question, we documented the diet, home range size, group sizes and composition, density, number of litters and body condition of lion tamarins living in cabruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 65 publications
3
65
0
Order By: Relevance
“…Floresta Azul (Sighting 1) is within the Serra dos Barbados range that rises to approximately 800 m, with cabruca forest occurring up to 700 m. The region of Arataca where L. chrysomelas was found (Sightings 2 and 3), is part a chain of mountains that includes the Serra das Lontras, the Serra dos Quatis and the Serra Javi where the maximum altitude is nearly 1,000 m. Cabruca is prevalent up to altitudes of 600 m. The region of Camacã where L. chrysomelas was found (Sighting 4) is located in the Serra do Baixão chain (west of Lontras) that rises up to 900 m and is composed of a mosaic of vegetation ranging from open pasture to mature forest. Cabruca is a habitat known to be used by L. chrysomelas and provides suitable resources throughout the species' range (Oliveira et al 2010(Oliveira et al , 2011Raboy et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Floresta Azul (Sighting 1) is within the Serra dos Barbados range that rises to approximately 800 m, with cabruca forest occurring up to 700 m. The region of Arataca where L. chrysomelas was found (Sightings 2 and 3), is part a chain of mountains that includes the Serra das Lontras, the Serra dos Quatis and the Serra Javi where the maximum altitude is nearly 1,000 m. Cabruca is prevalent up to altitudes of 600 m. The region of Camacã where L. chrysomelas was found (Sighting 4) is located in the Serra do Baixão chain (west of Lontras) that rises up to 900 m and is composed of a mosaic of vegetation ranging from open pasture to mature forest. Cabruca is a habitat known to be used by L. chrysomelas and provides suitable resources throughout the species' range (Oliveira et al 2010(Oliveira et al , 2011Raboy et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to potential resources for goldenheaded lion tamarins, several of the older rubber trees bear epiphytic bromeliads, providing potential microhabitats for insect foraging (Raboy and Dietz, 2004). Bromeliads are listed as principal foraging sites at all study areas where golden-headed lion tamarins have been observed (Raboy and Dietz, 2004;Guidorizzi, 2008;Oliveira et al, 2011;Catenacci et al, 2016). Although we did not record our study group foraging in bromeliads in the rubber plantation during the observation period described here, we observed this behaviour at a later time.…”
Section: Discussionmentioning
confidence: 69%
“…More recent studies have reported the species being able to survive and reproduce in secondary forests, including cabruca agroforests (Catenacci et al, 2016;Oliveira et al, 2011). Being predominantly a frugivore, the species' diet varies between areas, reflecting differences in floristic composition and plant density; this indicates that the species adapts easily to changes in fruit availability (Catenacci et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated number of golden-headed lion tamarins in 2009 was around 107 individuals [14]; however, this number may currently be higher because there have been four reproductive seasons since the survey and lion tamarins can produce twins in each reproductive season [18]. Also, the hybrids of the genus Cebus recorded by Cunha [12] have established populations mainly in the city of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 99%